1990
DOI: 10.1016/0005-2736(90)90183-o
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent fusion of the plasma membrane fraction from human neutrophils with liposomes

Abstract: A cell-free assay monitoring lipid mixing was used to investigate the role of Ca2+ in neutrophil membrane-liposome fusion. Micromolar concentrations of Ca2+ were found to directly stimulate fusion of inside-out neutrophil plasma membrane enriched fractions (from neutrophils subjected to nitrogen cavitation) with liposomes (phosphatidylethanolamine:phosphatidic acid, 4:1 molar ratio). In contrast, right-side-out plasma membranes and granule membranes did not fuse with liposomes in the presence of Ca2+. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…We showed in a previous report that plasma membranes can fuse with liposomes in a Ca2 -dependent manner (3). In this report, we show that the 36-kD protein both enhanced and inhibited this reaction.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We showed in a previous report that plasma membranes can fuse with liposomes in a Ca2 -dependent manner (3). In this report, we show that the 36-kD protein both enhanced and inhibited this reaction.…”
Section: Discussionsupporting
confidence: 65%
“…Annexin I did not promote lipid mixing between these membranes; however, it did affect lipid mixing between the plasma membrane fraction and liposomes. We and others have previously shown that plasma membranes fuse with liposomes in a Ca2l -dependent manner (3,21 ). The 36-kD protein enhanced Ca2 -dependent lipid mixing between plasma membranes and liposomes at 30 ,gM Ca2+ (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the conditions required for PMN activation have been extensively studied, much remains to be learned about the cofactors and mechanisms that promote fusion between granules and the plasma membrane. Recently it has been shown that Ca 2ϩ alone does not promote fusion between neutrophil granules and plasma membrane fractions using a cell-free fusion assay (3). Therefore, other components must be required to bring about phagolysosomal formation.…”
mentioning
confidence: 99%